Contamination of Soil with Pb and Sb at a Lead-Acid Battery Dumpsite and Their Potential Early Uptake by Phragmites australis - Abraham Jera; France Ncube; Artwell Kanda (Applied and Environmental Soil Science)
Recycling of spent Lead-Acid Batteries (LABs) and disposal of process slag potentially contaminate soil with Pb and Sb. Total and available concentrations of Pb and Sb in three soil treatments and parts of Phragmites australis were determined by atomic absorption spectrophotometry. Soil with nonrecycled slag (NR) had higher total metal concentrations than that with recycled slag (RS). Low available fractions of Pb and Sb were found in the soil treatments before planting P. australis. After 16 weeks of growth of P. australis, the available fractions of Pb had no statistical difference from initial values (p>0.05) while available Sb fractions were significantly lower when compared with their initial values (p<0.05). Metal transfer factors showed that P. australis poorly accumulate Pb and Sb in roots and very poorly translocate them to leaves after growing for 8 and 16 weeks. It may be a poor phytoextractor of Pb and Sb in metal-contaminated soil at least for the 16 weeks of its initial growth. However, the plant established itself on the metalliferous site where all vegetation had been destroyed. This could be useful for potential ecological restoration. The long-term phytoextraction potential of P. australis in such environments as LABs may need further investigation.